MENINGKATKAN KEUNGGULAN BERSAING USAHA KECIL DAN MENENGAH (UMKM) - R. Deni Muhammad Danial (JISPO : Jurnal Ilmu Sosial dan Ilmu Politik, 2017)
The economy of Sukabumi Regency from year to year is heavily influenced by development of Small and Medium Enterprises (SMEs). The SMEs are in the sector of service, trade and manufacture. Each year, the SMEs in Sukabumi Regency keep increased and can even be absorbing labor big enough. SMEs in the Regency of Sukabumi have proven resilience when it occurred Economic Crisis of 1998. Only the SME sector that survived from the collapse of the economy, while the bigger sectors were broken  by the crisis. However, the creation of employment by the SMEs in Sukabumi Regency and the amazing of the SMEs in defending themselves from the economic crisis, not accompanied with quality increase of their development mainly in the case of competitive advantage. Competitive advantage of SMEs in Sukabumi Regency generally operates experiencing problems. The problems are subscription with inefficiency of the cost, products without the unique which have the effect on the lack of competitiveness, and lack of concentration on the certain segments. The study provides findings that SMEs are business cultivated by many people, and SMEs become one of many hopes of society for improving their economical welfare. Thus, SMEs must have a competitive advantage in order to achieve solution to fix the economy of society. SMEs will have a competitive advantage if notice of at least 4 (four) elements namely: cost efficiency, product differentiation, rapid response and market focus. the components can be sorted based on the priority, as follows: product differentiation, market focus, cost efficiency and rapid response.